2023
DOI: 10.3390/agronomy13123016
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Tomato Crop and Water Productivity to Deficit Irrigation Strategies and Salinity Stress in Greenhouse

Akram K. Alshami,
Ahmed El-Shafei,
Abdulrasoul M. Al-Omran
et al.

Abstract: Saudi Arabia faces water scarcity and inadequate sustainable sources, particularly in agriculture, necessitating efficient irrigation water management to improve productivity amidst rising demand. The study investigated the impact of irrigation levels and water salinity on tomato plants in greenhouses, covering four irrigation levels (100%, 80%, 60%, and 40% of ETc) and three water sources (FW (0.9 dS·m−1), SW (3.6 dS·m−1) and MW (2.25 dS·m−1)). Salinity impacts crop yield, physiological responses, and fruit q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
6
1

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 77 publications
5
6
1
Order By: Relevance
“…Osmotic stress causes a drop in Chl-I levels, which damages chloroplast layers by increasing the membrane permeability [48]. These results are in line with previous studies, which have demonstrated that environmental stressors, including dryness and salt stress, cause tomato leaves to lose their photosynthetic pigments [31,49].…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Osmotic stress causes a drop in Chl-I levels, which damages chloroplast layers by increasing the membrane permeability [48]. These results are in line with previous studies, which have demonstrated that environmental stressors, including dryness and salt stress, cause tomato leaves to lose their photosynthetic pigments [31,49].…”
Section: Discussionsupporting
confidence: 91%
“…The deficit irrigation considerably reduced the h, WS w , WS d , LA, and ST, indicating the mechanisms intended for conserving water, such as decreased expansion of cells, altered hormonal balance, and resource allocation prioritizing surviving overgrowth [61,62]. This finding was in line with earlier studies by Agbna et al [20], Chand et al [22], Colimba-Limaico et al [63], Wu et al [64], and Alshami et al [31], which indicate that salinity and water stress cause a considerable loss of many morphological characteristics. The magnitude of this reduction is influenced by the level and duration of the irrigation stress.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations